Otimização e proposta de um nanocarreador da naftoquinona 6B,7-dihidro-5Hciclopenta[B]nafto[2,1-D]furano-5,6 (9AH)-diona e avaliação de seu potencial farmacológico in silico e in vitro - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Developing a drug is a long, complex and costly process, where it is necessary to evaluate the pharmacokinetic, toxicological and molecular characteristics of drug candidates to succeed during the process. 6b,7-dihydro-5H-cyclopenta[b]naphtho[2,1-d]furan5,6(9aH)-dione (CNFD) is a semi-synthetic naphthoquinone that exhibits cytotoxic activity against breast cancer cells (MCF )-7) and melanoma (SK-Mel-19, SK-Mel-28, SK-MEL-103 and B16F10), and antitumor in a murine model of melanoma, being considered a promising molecule for use as a drug. However, its low yield of restriction control reaction regarding its large-scale application, as well as its physicochemical characteristics may affect its pharmacokinetic and technological characteristics. Thus, this project photographed the process of obtaining CNFD and its pharmacokinetic and technological characteristics through the development of a nanocarrier system. Therefore, they were analyzed in silico for the prediction of pharmacokinetic and pharmacological parameters, as well as the optimization of the process of obtaining CNFD, development and characterization of polymeric nanoparticles containing CNFD and the in vitro evaluation of cytotoxicity, and influence on the glucose and lipid metabolism. From the results obtained, the optimization of the synthesis of CNFD was obtained, which it was possible to reach a yield of 48.16 ± 1.58% after 1 hour of reaction, being higher than that found in the literature, which is 15% after 3 hours of reaction, in addition, CNFD has a high rate of intestinal absorption (97%) and strong binding to plasma proteins (93%) without inhibiting P-glycoprotein, showing specificity and complementarity in the sequence of CYP1A2, 2C19 and 2C9 in phase 1 metabolism. Nanospheres are more stable models for CNFD encapsulation than nanocapsules, presenting acceptable technological standards that did not change significantly during the 5 months analyzed, in addition to presenting cytotoxicity against receptors neoplastic cells by a mechanism that does not involve the influence of CNFD on glucose and lactate dehydrogenase metabolism in the tumor microenvironment.
Optimization and proposal of a naphthoquinone 6B,7-dihydro-5Hcyclopenta[B]naphtho[2,1-D]furan-5,6 (9AH)-dione nanocarrier and evaluation of its pharmacological potential in silico and in vitro
Keywords: Naftoquinonas; Simulação de acoplamento molecular; Nanotecnologia; CIENCIAS DA SAUDE: FARMACIA; Naftoquinona; Nanotecnologia; Atividade biológica; Docking molecular